(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2024)
The present work deals with the carnivorans found in five Neogene localities in eastern Romania: the Vallesian locality of Păun, the Turolian localities of Pogana 1 and Creţeşti 1, and the Ruscinian localities of Bereşti and Măluşteni. The presented material includes cranial and postcranial specimens, some of which are herein described for the first time. This study includes a re-description and re-depiction of the type material of Lutra rumana Simionescu, 1922 and Promephitis malustenensis Simionescu, 1930, in order to clarify the taxonomic position of these two enigmatic taxa. The carnivoran faunal lists of all five localities are reviewed offering interesting insights into the temporospatial range of the discovered forms. Most localities have only yielded a limited number of species, except from Măluşteni, which shows evidence of at least nine different coexisting forms. Notable occurrences in terms of biostratigraphy include Paludolutra sp. in Pogana 1, Protictitherium crassum (Depéret, 1892) in Creţeşti 1, and a phocid from Măluşteni. This review aims to aid the understanding of the Neogene ecosystems in the north of the Paratethys in terms of faunal contents, biostratigraphy and palaeoecology.